2020
DOI: 10.1109/access.2020.2974693
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study on Influencing Factors of Knowledge Product Remixing in OIC

Abstract: Remixing of knowledge products has become one of the mainstream innovation models for the online innovation community (OIC). It is of great significance to explore the influencing factors of knowledge product remixing in OIC for better stimulating the open innovation. We first propose an analytical model for influencing factors of knowledge product remixing, then come up with a method for identifying false product attributes based on deep learning, and finally sum up the influencing factors of knowledge produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Secondly, psychological ownership drives such transition. Specifically, when community users generally with collaborative psychology allow other users to remix their knowledge-intensive works for the purpose of innovation, they will desire to monopolize the works, also known as psychological ownership ( Feng et al, 2019 ; Tan et al, 2020 ). Excessive psychological ownership will entail conflicting psychology and force other users to search for other options of poorer quality for the purpose of remix.…”
Section: Empirical Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, psychological ownership drives such transition. Specifically, when community users generally with collaborative psychology allow other users to remix their knowledge-intensive works for the purpose of innovation, they will desire to monopolize the works, also known as psychological ownership ( Feng et al, 2019 ; Tan et al, 2020 ). Excessive psychological ownership will entail conflicting psychology and force other users to search for other options of poorer quality for the purpose of remix.…”
Section: Empirical Results and Analysismentioning
confidence: 99%
“…Firstly, while some scholars analyze the attributes of user-generated content ( Dasgupta et al, 2016 ; Stanko, 2016 ) and the impact of user-generated content heterogeneity on remix performance ( Kim et al, 2016 ; Flath et al, 2017 ; Voigt, 2018 ), they fail to probe in the mechanism of user knowledge endowment on remix. Secondly, the relationship between the diffusion ( Stanko, 2016 ; Tan et al, 2020 ), transfer ( Flath et al, 2017 ), and spillover ( Kyriakou et al, 2017 ) of knowledge in OCC and user remix can account for the advantages of user remix derived from the heterogeneous knowledge endowment, albeit the process mechanism of user knowledge endowment in driving remix remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Logically, consumers may find that products that are (even somewhat) familiar tend to be easier for them to use (Rogers, 2003). This is part of what Tan, Miao, and Tan (2020) refer to as a remixed product's “inheritance” from its parent. With respect to value, it also seems reasonable that the availability of sibling designs could potentially lead to price competition since sibling products may vie for the same potential customers.…”
Section: Hypothesesmentioning
confidence: 95%
“…A deeper understanding of the mediating effects of GC and interaction also requires consideration of the online open collaboration contexts. Tan et al (2020) suggested that knowledge complexity (KC) is critical for understanding open collaboration in online selforganizing platforms. Knowledge complexity refers to the degree of difficulty in understanding and applying the task-related knowledge content when a user performs a task in online self-organizing platforms (Tan et al, 2020).…”
Section: Factors Influencing Group Open Collaborationmentioning
confidence: 99%
“…Tan et al (2020) suggested that knowledge complexity (KC) is critical for understanding open collaboration in online selforganizing platforms. Knowledge complexity refers to the degree of difficulty in understanding and applying the task-related knowledge content when a user performs a task in online self-organizing platforms (Tan et al, 2020). When knowledge comprises many elements interacting richly, it will lead to a diversity of results caused by users' differences through clicking, browsing, discussing and forwarding knowledge.…”
Section: Factors Influencing Group Open Collaborationmentioning
confidence: 99%